Elementary Statistics: Picturing the world - Ran Larson (Pearson, 2015)
For algebra-based introductory statistics courses, statistics opens a window to the modern world, and this market-leading text makes it easy to understand! This text provides stepped out instruction, real-life examples and exercises, and the use of technology to offer the most accessible approach. The authors carefully develop theory through strong pedagogy, and examples show how statistics is used to picture and describe the world. In keeping with the premise that students learn best by doing, it includes more than 210 examples and more than 2300 exercises, to make the concepts of statistics a part of students' everyday lives.